Segmentation Of Retinal Vasculature Using Contourlet Enhancement For Early Detection Of Diabetic Retinapthy - Ahmad Aliff B Abd Ghani, Ahmad Aliff (Universiti Teknologi Petronas, 2010)
In this project we use contourlet transform rather than wavelet transform because the contourlet transform was proven to require less number of coefficient compared to wavelet and contourlet also have the ability to detect directional signal. The enhanced blood vessel will be extract by BottomHat. This transformation works by isolating dark object on light surrounding.